2017
DOI: 10.1002/ange.201701115
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable and Regenerable Platinum–Tin Clusters for Propane Dehydrogenation Prepared by Atom Trapping on Ceria

Abstract: Ceria (CeO 2 )s upports are unique in their ability to trap ionic platinum (Pt), providing exceptional stability for isolated single atoms of Pt. The reactivity and stability of single-atom Pt species was explored for the industrially important light alkane dehydrogenation reaction. The singleatom Pt/CeO 2 catalysts are stable during propane dehydrogenation, but are not selective for propylene.D FT calculations show strong adsorption of the olefin produced, leading to further unwanted reactions.Incontrast, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 38 publications
7
88
0
Order By: Relevance
“…This figure predicts the minimum required binding energies of single atoms (examples given for Pt, Pd, and Ni) on a support to obtain stable SACs for a day at the two indicated temperatures. In this study, we focused on idealized surfaces without defects (except for steps), hydroxyl groups or dopants, which may act as nucleation sites for sintering and in this way alter diffusion processes of metal adatoms [35][36][37] . Despite this simplification, the framework introduced is general and the correlations provide a guiding tool for initial materials selection.…”
Section: Stability Assessmentmentioning
confidence: 99%
“…This figure predicts the minimum required binding energies of single atoms (examples given for Pt, Pd, and Ni) on a support to obtain stable SACs for a day at the two indicated temperatures. In this study, we focused on idealized surfaces without defects (except for steps), hydroxyl groups or dopants, which may act as nucleation sites for sintering and in this way alter diffusion processes of metal adatoms [35][36][37] . Despite this simplification, the framework introduced is general and the correlations provide a guiding tool for initial materials selection.…”
Section: Stability Assessmentmentioning
confidence: 99%
“…Actually, despite the superior catalytic performance of single‐atom catalysts in many reactions of commercial importance, 13,21‐32 the nature of the active phase is not always clear, which is due primarily to the increased complexity in the electronic structure that arises from the change in surface composition 33 . For instance, it has been demonstrated that coadsorption of a pair of amphoteric species (e.g., propyl and H in PDH) could be significantly more stable than the adsorption of the isolated species on many oxide surfaces due to Lewis acid–base interaction, 34‐36 which makes it possible to tailor the catalytic properties of oxides to a particular chemical reaction by doping the surfaces with single metal atoms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, much industrial chemical research has being devoted to the search for new and more effective catalysts because Pt is rather costly and hexavalent Cr is environmentally unfriendly. Hence, many oxides such as Ga 2 O 3 , 4‐6 VO x , 7‐9 ZrO 2 , 10‐12 CeO 2 , 13,14 ZnO, 15 TiO 2 , 16 and Al 2 O 3 17 have been extensively studied for PDH, among which Ga 2 O 3 is a very promising candidate.…”
Section: Introductionmentioning
confidence: 99%
“…27 − 30 Very recently, a method based on atomic trapping was developed for the preparation of highly dispersed Pt, even at atomic level. 31 33 It was reported that the oxidized Pt species can disperse as single atoms on a CeO 2– x support upon calcination at 800 °C under air. The obtained catalyst showed excellent catalytic performance in the low-temperature oxidation of CO and in the conversion of methane into C 2 hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%